Systemic allergic reactions induced by labile plant‐food allergens: Seeking potential cofactors. A multicenter study. Issue 5 (1st November 2020) - Asero, Riccardo; Ariano, Renato; Aruanno, Arianna; Barzaghi, Claudio; Borrelli, Paolo; Busa, Moira; Celi, Giorgio; Cinquini, Massimo; Cortellini, Gabriele; D'Auria, Francesca; De Carli, Marco; Di Paolo, Camilla; et al.
Abstract: Background: Heat‐and‐pepsin‐sensitive plant food allergens (PR‐10 and profilin) sometimes cause systemic reaction. Objective: To detect the risk factors for systemic reactions induced by labile food allergens. Methods: A retrospective multicenter study was performed on patients with a documented history of systemic allergic reaction to labile plant food allergens and on age‐matched controls with a history of oral allergy syndrome (OAS) induced by the same foods. Offending foods, their amount, and state (solid or liquid), and potential cofactors (nonsteroidal anti‐inflammatory drugs, protonic pump inhibitors, exercise, alcohol, and fasting) were considered. Results: We studied 89 patients and 81 controls. Sensitization to PR‐10 or profilin, IgE to Bet v 1 and/or Bet v 2, and foods causing OAS were similar in the two groups. Twenty patients experienced >1 systemic allergic reaction. Tree nuts, Rosaceae, Apiaceae, and soymilk were the main offending foods. Seventeen (19%) patients were taking a PPI when the systemic reaction occurred (vs 5% in controls; P < .025). The ingestion of the offending food in liquid form (soymilk) was frequent among patients (15%) but unusual among controls (2%; P < .025). Soy milk‐induced systemic reactions were independent of PPI treatment. Fasting and excess of allergen, but not NSAID and exercise, were other relevant cofactors for systemic reactions. Systemic reactions occurred without any identifiable cofactor in 39 (44%) cases. Conclusion: PR‐10‐ and profilin‐induced systemic reactions are facilitated by PPI, ingestion of large amounts of unprocessed foods, and fasting. Soybean beverages represent a risk for PR‐10 hypersensitive patients and should be avoided. Abstract : Hypersensitivity to labile plant‐food allergens (PR‐10 and profilin) secondary to pollen allergy frequently causes oral allergy syndrome. Labile allergens may become dangerous when the raw foods are ingested in excessive amounts or in liquid form. Other cofactors include therapy with proton pump inhibitors and fasting. The most frequently involved foods are as follows: tree nuts, Rosaceae, Apiaceae, and soy milk. Abbreviations: NSAID, non‐steroidal anti‐inflammatory drugs; PPI, proton pump inhibitors; PR‐10, pathogenesis‐related proteins group 10